Korelasi Kajian Fisikokimia Ekstrak Klika Faloak (Sterculia populifolia DC.) Menggunakan Variasi Pelarut Terhadap Penghambatan Bakteri Patogen - Reny Syahruni; Syamsu Nur; Akhmad Amrullah; Novianti Tonapa; Vivi Shelina (Universitas Tadulako, 2018)
Faloak (Sterculia populifolia DC.) is one of species of sterculiaceae found in East Nusa Tenggara which has potential as a medicinal plant mainly as an antimicrobial. This study aims to determine the correlation of physicochemical study of faloak bark extracts with variation of solvents in inhibiting of pathogenic bacteria. The sample was extracted by maceration method with different polarity level of solvents i.e acetone, acetone 70%, water, ethanol 96%, ethanol 70% and ethanol 50%. The results of extraction through maceration indicate the difference of yield recovery from each of the extraction solvents. The highest yield was obtained from 70% ethanol extract, while the lowest yield of acetone extract. The increase of solvent polarity in this study did not give effect to the amount of recovery of yield. It is also seen from the highest total phenolic content obtained from 70% acetone extract while the lowest in aquadest extract. The antibacterial activity of faloak bark extract on Salmonella typhi was tested using agar diffusion method with 1% of extract solution. Both of ethanol 96% and acetone extracts did not show any inhibitory activity. The largest inhibitory activity was demonstrated by 50% ethanol extract. The polarity level of the extract, the level of total phenolic content and the magnitude of rendement  did not show correlation of increased inhibitory activity on Salmonella thypi as well.